A Metagenomic Survey of Virological Hazards in Market-Ready Oysters - René A. M. Dirks; Nils P. Sosef; Johanna T. M. Zwartkruis-Nahuis; Marijke M. A. Thijssen; Claudia C. C. Jansen; Ingeborg L. A. Boxman (Food and Environmental Virology, 2025)
Viral contamination of bivalve molluscs, such as oysters, is a well-recognized food safety risk. The aim of this study was to assess virological hazards in market-ready oysters on the Dutch market. Non-targeted metagenome analysis was first performed on norovirus spiked-in samples showing linear and sensitive detection of norovirus GI.2 and GII.4 down to 14 and 5 genome copies per reaction, respectively. Subsequently, metagenomic measurements were performed to detect vertebrate viral genomes present in 24 undepurated B-area samples and 144 market-ready oyster samples taken in November up to and including February of the years 2015–2021. Genome sequences from fifteen viral species were identified in market-ready oysters which are associated with infections in humans and were detected above the genomic coverage threshold (5%) applied. Among these, the two genera from the Caliciviridae family, norovirus and sapovirus were detected at high prevalence (44 and 30%). Additionally, adeno-associated dependoparvovirus A and B as well as Aichi virus A and B (ribo)nucleic acids were detected (42, 33, 6, and 11%). Nucleic acids from virus species in oysters included potentially hazardous Picobirnavirus, Anellovirus, and multiple Circoviridae and Genomoviridae species. By integrating metagenome analysis into the monitoring process, researchers, food producers and regulatory bodies can gain valuable insights into the viral communities present in the food chain. This allows for the detection of potential pathogenic hazards at an early stage, providing an opportunity for tailored monitoring programs and targeted interventions to maintain the sanitary quality of the production area and safeguard public health.

Successful Use of Advertisement Pictures to Assist Recall in a Food-Borne Hepatitis A Outbreak in The Netherlands, 2017 - Madelief Mollers; Ingeborg L. A. Boxman; Harry Vennema; Ife A. Slegers-Fitz-James; Diederik Brandwagt; Ingrid H. Friesema; Jenny S. Batstra; Margreet J. M. te Wierik (Food and Environmental Virology, 2018)

Human Enteric Viruses Occurrence in Shellfish from European Markets - Ingeborg L. A. Boxman (Food and Environmental Virology, 2010)